ASSESSING THE SAFETY USE OF HERBICIDES BY HORTICULTURAL FARMERS IN RIVERS STATE, NIGERIA - Iyagba, A.G. (European Scientific Journal, ESJ, 2013)
Herbicides though beneficial to farmers in weed control they could also be harmful to the users and the environment. It was therefore necessary to determine the level of herbicide use and access the safety methods applied by horticultural farmers in Rivers State, Nigeria. Assessment of the safety use of herbicides by horticultural farmers in Rivers State of Nigeria was carried out in the 2006 farming season. Structured questionnaires were administered to farmers in the three Agricultural Zones of the State. The survey revealed that most of the horticultural farmers in the state were within the age of 14 – 50 years (48%), were married (70%), were females (60%), secondary school leavers (40%), most did not use herbicides (63%) and having used herbicides for the past 1-5 years (45%). The results further showed that most of the farmers obtained their herbicides from the open market (55%), agreed that herbicides are time saving (52%), applied with CP-15 (53%), which were borrowed (48%) and use the milk measurement (40%). Majority of the farmers use protective wears (58%), talking during application (51%) discard left over spray mixture into the rivers/seas (39%), wash and sell the containers (36%), wash their sprayers (70%), bath after application (73%), experienced low crop injury (23%), encountered accidents (77%), through the skin (72%) and limited knowledge of herbicide use as the greatest constraints to safety use of herbicides by farmers. Herbicide use among horticultural farmers in the state is low, enlightenment programme on health and safety use of herbicide is needed.